Interviewing Fernando Argenta. (Journal of Parents and Teachers, 2014)
This article interviews Fernando Argenta, director of the Popular Classics program on National Radio, with the aim of knowing his point of view on education in music, classical music and children, music and family, therapy Musical and other aspects related to this topic.
Keywords: Interview; Fernando Argenta; music; music education.